Teaching English Through Islamic Values and Technology: Evaluating Toy Theater's Impact in Islamic Education - Ambarini, Ririn; Hidayat, Nur; Utami, Hadi Riwayati; Zahraini, Dian Ayu (English Education Department, 2025)
This study aims to examine the effectiveness of using the Toy Theater application in teaching English integrated with Islamic values in Islamic-character schools. Utilizing a mixed-methods approach, the research involved 30 students as subjects to evaluate vocabulary improvement using pre-test and post-test methods. The results revealed a significant increase in students' vocabulary scores, with an average improvement of 27.1 points after using Toy Theater. Additionally, qualitative analysis through interviews and observations revealed that students felt more motivated and engaged in learning, and experienced a reinforcement of Islamic values during the process. These findings confirm that interactive technology can be used to strengthen religious teaching and enhance language skills simultaneously, making this method innovative in the context of Islamic education.